Automated Crack Detection and Crack Growth Rate Measurement Using Thermoelasticity. (2017) - Rajic, Nik; Brooks, Chris
Abstract: A new capability for automated crack detection and crack growth rate monitoring is described and experimentally validated. The capability is based on a low-cost industrial grade microbolometer mounted to an x-y linear slider assembly driven by a guidance algorithm that uses the thermoelastic quadrature signal to locate the crack tip. The approach furnishes a high density record of the crack path, as well as thermoelastic response imagery in the vicinity of the crack tip which can be used to determine stress intensity factors. The performance of the system is compared to that of travelling microscopy and shown to be similar at crack growth rates above 10 -7 m/cycle, but inferior at lower rates due to increased scatter in the location estimates. This scatter is attributed in part to the limited spatial resolution of the system in its present configuration.